2022
DOI: 10.1109/tns.2021.3132402
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Tolerant Digitally Controlled Ring Oscillator in 65-nm CMOS

Abstract: This paper presents a radiation-tolerant digitally controlled CMOS ring oscillator design suitable for All-Digital Phase-Locked Loop (ADPLL) implementations. To address the challenges presented by harsh radiation environments, a wide tuning range oscillator architecture is presented with superior Single-Event Effect (SEE) tolerance. The proposed oscillator circuit is characterized experimentally in a 65 nm technology and shown to achieve a significant reduction in SEE sensitivity up to a Linear Energy Transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In Sect. 3, we applied the proposed model to a ring oscillator circuit [16][17][18][19] and confirmed that it can reproduce the changes in circuit characteristics that occur during irradiation. In Sect.…”
Section: Introductionmentioning
confidence: 54%
“…In Sect. 3, we applied the proposed model to a ring oscillator circuit [16][17][18][19] and confirmed that it can reproduce the changes in circuit characteristics that occur during irradiation. In Sect.…”
Section: Introductionmentioning
confidence: 54%
“…found for this circuit at the point of failure. The DCRO ADPLL hence failed to obtain lock as soon as the maximum oscillation frequency became insufficient to provide the desired value [8]. The LC DCO in comparison showed a radiation-induced frequency shift of less than 1%.…”
Section: Jinst 18 C01060mentioning
confidence: 99%
“…This segmentation distributes devices sensitive to charge collection spatially, causing only a small subset to be affected by any given SEE. To further suppress the phase displacement from SEEs, we proposed to add an additional series resistor in series with the output of each unit cell, which provides additional decoupling of unit cells from one another, as reported in [8]. The oscillator provides 9 bit frequency control range with linear tuning characteristics at an LSB size of 3.5 MHz.…”
Section: Digitally Controlled Ring Oscillator (Dcro)mentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous reduction in the feature size of integrated circuit devices and the rapid development of the aerospace industry, the phase-locked loop (PLL) operated in the radiation environment is seriously affected by the single-event effect, which cannot be ignored [1,2]. When high-energy particles act on the PLL, it will induce the singleevent effect, which will make the frequency and phase of the output signal of the PLL drift and cause the circuit system function to be abnormal [3][4][5]. Each module of the PLL has a different response to the single-event effect [6,7].…”
Section: Introductionmentioning
confidence: 99%